Fluid environment for preservation of pore spaces in a deep dolomite reservoir. Issue 4 (4th December 2014) - Zhu, D.; Meng, Q.; Jin, Z.; Hu, W.
Abstract: Well TS1 reveals many uncemented pores and vugs at depths of more than 8000 m in a deep Cambrian dolomite reservoir in the Tarim Basin, northwestern China. The fluid environment and mechanism required for the preservation of reservoir spaces have yet not been well constrained. Carbon, oxygen, and strontium isotope compositions and fluid inclusion data suggest two types of fluids, meteoric water and hydrothermal fluid, affecting the Lower Paleozoic carbonate reservoirs in the Tarim Basin. Based on simulation using a thermodynamic model for H2 O‐CO2 ‐NaCl‐CaCO3 system, meteoric water has the ability to continuously dissolve carbonate minerals during downward migration from the surface to deep strata until it reaches a transition depth, below which it will begin to precipitate carbonate minerals to fill preexisting pore spaces. In contrast, hydrothermal fluid has the ability to dissolve carbonate in deep strata and precipitate carbonate in shallow strata during upward migration. Based on the dissolution–precipitation characteristics of the two types of fluids, the ideal fluid environment for the preservation of preexisting reservoir spaces occurs when carbonate reservoir is neither in the CaCO3 precipitation domain of meteoric water nor in the CaCO3 precipitation domain of hydrothermal fluid. Taking the Lower Paleozoic carbonate reservoirs in the north uplift area as an example, the spaces in the deep Cambrian dolomite reservoir near well TS1 were seldom filled because thick Ordovician deposits blocked meteoric water from migrating downward into the Cambrian dolomite reservoir and because the Cambrian dolomite reservoir has been in the domain of hydrothermal dissolution since the Permian. The deep carbonate layers in basins elsewhere with a similar fluid environment may have high uncemented porosity and consequently have good hydrocarbon exploration potential. Abstract : Both meteoric water and hydrothermal fluid affected the deep Cambrian dolomite reservoir in the Tarim Basin. The fluid environment for preservation of preexisting pore spaces occurs when the deep reservoir is in CaCO3 dissolution domain of hydrothermal fluid but not in precipitation domain of meteoric water.